A circulação de cinco obras clássicas de poesia infantil brasileira publicadas entre 1940 e 1980: análise de estratégias para a permanência e acomodação dentro e fora do contexto escolar - Raquel Cristina Baêta Barbosa (2019)
This research had the objective to investigate factors that contributed to the permanence, in different versions, in the publishing market and field of the Brazilian children's literature, of the works O menino poeta (1943) of Henriqueta Lisboa, Ou isto ou aquilo of Cecília Meireles (1964), Pé de pilão (1968) by Mario Quintana, A Arca de Noé (1970) by Vinicius de Moraes and É isso ali (1984) by José Paulo Paes, published between the decades of 1940s and 1980s of the twentieth century. Ultimately, it is intended to understand what makes a work of children's poetry become a classic, that is, how the construction of its historical recognition, the sedimentation of its quality and the fact that it is taken as a reference and basis for other productions. To understand these factors, a communication circuit was built for these works of Brazilian children's poetry. The research was based in a historical perspective, taking as a major reference the contributions of history books and history of children's literature. The methodology was focused on the categorization and analysis of data based on the methodological path named communication circuit, proposed by Darnton (1990). Besides documentary sources, questionnaires were also applied to teachers from the initial years and librarians working in the municipal schools of Belo Horizonte. The points focused on the circuit were: economical, cultural, educational and social interferences, in the period in which the works were launched; the authors and their productions, books and their versions, publishers and their actors, poetic anthologies and Portuguese textbooks, ratings, awards and literary criticism, recommendations from specialists and the public in general, government book-reading programs, catalogs of virtual bookstores, the presence of these books in schools and in school libraries, teachers as mediators of reading and, finally, the possibility of the reader accessing the works indirectly . The choice of these instances aimed to identify, from the analysis of different internal and external aspects to the production and circulation of five works of Brazilian children's poetry, factors that contribute to their permanence, in varied versions, reaching different generations of readers. The results show that the works continue to circulate and are reedited by the recognition and symbolic value of the authors and their productions and, consequently, by the strength of the literary text, by the re-readings of the works by different illustrators and the different editorial and graphic interventions in the various proposals, with additions and suppressions. In this way, there are various adaptations in materiality, paratexts and illustrations to make the works renew and circulate in different periods. Another factor relates to the relevance of the instances that evaluate, select and indicate the works, as well as the presence of poems and parts of the works in textbooks, poetic anthologies and other materialities as a form of dissemination, accommodation and legitimation. And finally, there was the presence of the books in school libraries arising from government to encourage reading programs, guaranteeing access and the formation of the literary reader.